Effort to Stop the Impact of Mining Activities Without Permission in Perspective Fulfilling the Right to the Good and Healthy Environment - AS, Yenny; Arabiyah, Syariah; Yuliastini, Anita; Dawi, Klara; Damaryanti, Henny (Opción, 2019)
Unlicensed mining has a very bad impact on people’s lives. One of my in- terests is the destruction and / or pollution of the environment, so that the surrounding communities are in a bad and healthy environment. The focus of the issues raised is the impact of mining activities without these permits on the quality of environmental support resources, especially on fulfilling the right to a good and healthy environment for the community, and what policies can be carried out by the Government and relevant stakeholders. Through the socio legal research approach, it was found the fact that people living in the area around the mine were in a bad and healthy environment, where there were results of research that had been revealed on the nails and hair of people in the area around the mining area without indications of methyl mercuri. From the health aspect, this is certainly harmful and disturbs health. Not to men- tion the other environmental impacts that have resulted in the fulfillment of the right to a good and healthy environment as a human right being ignored. Responding to these issues as a manifestation of state responsibility requires the handling of an integrated and sustainable and releasing the sectoral ego.